2016
DOI: 10.1109/tip.2016.2516953
|View full text |Cite
|
Sign up to set email alerts
|

A Retinal Mechanism Inspired Color Constancy Model

Abstract: In this paper, we propose a novel model for the computational color constancy, inspired by the amazing ability of the human vision system (HVS) to perceive the color of objects largely constant as the light source color changes. The proposed model imitates the color processing mechanisms in the specific level of the retina, the first stage of the HVS, from the adaptation emerging in the layers of cone photoreceptors and horizontal cells (HCs) to the color-opponent mechanism and disinhibition effect of the non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 61 publications
0
32
0
Order By: Relevance
“…A biologically inspired model for colour constancy was reported by Gao et al [39] that exploits the response of the Double Opponent cells in different channels and estimates the colour of the illuminant by max or sum pooling mechanism in long, medium and short wavelength colour space. An improved retinal-mechanism-based model was proposed by Zhang et al [40]. The authors imitated the function of Horizontal Cell (HC) modulation that provides global colour correction with cone-specific lateral gain control.…”
Section: Related Workmentioning
confidence: 99%
“…A biologically inspired model for colour constancy was reported by Gao et al [39] that exploits the response of the Double Opponent cells in different channels and estimates the colour of the illuminant by max or sum pooling mechanism in long, medium and short wavelength colour space. An improved retinal-mechanism-based model was proposed by Zhang et al [40]. The authors imitated the function of Horizontal Cell (HC) modulation that provides global colour correction with cone-specific lateral gain control.…”
Section: Related Workmentioning
confidence: 99%
“…High priority -It is generally suggested that the ganglion cells within the retina are the basis of color processing mechanisms of human color constancy, which respond to the activations of cone photoreceptors at the very first stage of the human visual system [3,17]. Therefore, it makes more sense to perform the computational color constancy before the explorations of further semantic information.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the photosensors in modern digital cameras do not possess the ability of automatically compensating for the illuminant colors. To address this issue, a variety of computational color constancy algorithms have been proposed to mimic the dynamical adjustments of the cones in the human visual system [1,2,3].Computational color constancy generally works by first estimating the illuminant color, and then compensating it by multiplying the reciprocal of the illuminant color to the color-biased image. Existing computational color constancy algorithms can be classified into a priori assumption-based ones and learning-based ones, according to whether a training process is needed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The biological color constancy method is intended to mimic and apply the functional characteristics of the human visual system (HVS) to perform the learning-based illuminant estimation, and several models have been presented [32][33][34]. Gao et al [32] propose an HVS-based color rendering approach by taking after the interaction between the single-opponent (SO) cells in the retina, the double-opponent (DO) cells and any possible neurons in the human visual cortexes.…”
Section: Introductionmentioning
confidence: 99%